„ZWISCHEN DEN ZEILEN GELESEN“. Funktionen von Phraseologismen in Feuilletons der »Frankfurter Allgemeinen Zeitung« - Urban, Anna (Wydawnictwo Naukowe UAM, 2009)
The book focuses on functions of modifi ed and nonmodifi ed idioms encountered in feuilletons of the national German newspaper »Frankfurter Allgemeine Zeitung«. The author discusses the fundamental issues of terminology and classifi cation of phraseological units, their ambiguity, the difference between modifi cation and variability, as well as systemizes the typology of idiomatic modifi cation with a number of subordinate aspects. Then the author assigns pragmatic functions perceptible in the dialogue between the author and the recipients as well as functions of text structuring. The book comprises an extensive collection of fi ve hundred idioms in their textual environment. This approach highlights the enormous potential of idioms under the activation of general knowledge as well as interpretative fi nesse. The author comprises the crucial features of feuilletons making the canonic variant of the genre model.
„Read between the lines“. Functions of idioms in feuilletons of »Frankfurter Allgemeine Zeitung«